Types and functions of phraseology in the Kazakh and Turkish languages (based on the work of B. Sokpakbayev "Journey to childhood") - Omirbekova, Ж.; Serdalina, С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
This article is based on the work of Berdibek Sokpakbayev, one of the prominent writers of Kazakh literature, entitled “Balalyk shakka sayahat”. In this work, the meanings of the Kazakh-Turkish phraseological units defined in the book were studied, and the Turkish equivalents of these regular expressions were to be given. First of all, in order to perform translation in the correct way, translator’s ability to offer the connection between sentence elements, commutative/ idiomatic expressions in words and words groups is important. When translating idioms, it is important that translator does not lose the meaning of phrase in the source language. Therefore, another purpose of the research will be identify translation problem encountered between dialect and idiom and show solutions. When the Kazakh Turkish and Turkish idioms are compared, it is also noteworthy that common idioms between the two dialects, different meaningful idioms are established with formally similar looking. This indicates the existence of “trap words” as well as “trap idioms”, which are accepted from false equivalents in inter-dialect translations.